Antimicrobial efficacy of low concentration PVP-silver nanoparticles deposited on DBD plasma-treated polyamide 6,6 fabric - Ribeiro, Ana Isabel Ferreira (2019)
In this study, a low concentration (10 μg·mL−1) of poly(N-vinylpyrrolidone) (PVP)-coated silver nanoparticles (AgNPs) were deposited by spray and exhaustion (30, 70 and 100 ◦C) methods onto untreated and dielectric barrier discharge (DBD) plasma-treated polyamide 6,6 (PA66) fabric. DBD plasma-treated samples showed higher AgNP deposition than untreated ones for all methods. After five washing cycles, only DBD plasma-treated samples displayed AgNPs on the fabric surface. The best-performing method was exhaustion at 30 ◦C, which exhibited less agglomeration and the best antibacterial efficacy against S. aureus (4 log reduction). For E. coli, the antimicrobial effect showed good results in all the exhaustion samples (5 log reduction). Considering the spray method, only the DBD plasma-treated samples showed some bacteriostatic activity for both strains, but the AgNP concentration was not enough to have a bactericidal effect. Our results suggest DBD plasma may be a low cost and chemical-free method for the preparation of antibacterial textiles, allowing for the immobilization of a very low—but effective—concentration of AgNPs.